Current Scenario and Perspective of Teaching Chinese at Confucius Institutes in Pakistan - Hanif, Bushra (Pakistan Journal of Humanities and Social Sciences, 2023)
Due to the progressive economic development and open-up policy along with the “one belt one road” initiative, the trend of learning Chinese is increasing throughout the developing world. The long-lasting China-Pakistan friendship and the initiation of the China-Pakistan Economic Corridor illuminated the future job market for Chinese-Urdu translators. This scenario urged Pakistani youth to learn the Chinese language at large. This increasing thrust for Chinese learning was contented with the establishment of various Confucius Institutes (CI) and Confucius classrooms in several universities. Confucius Institute at the National University of Modern Languages (NUML) is the pioneer institute which was established in 2005 followed by many others. Currently, 5 Confucius institutes have been established at the University of Punjab, Agricultural University Faisalabad, Karachi University, and Sargodha University besides NUML. In addition, various short courses have also been started in various vocational training institutes (VTI) established under technical and vocational training authorities to serve as secondary-level Chinese teaching centers. Currently, 94 centers are being operated all over Pakistan to provide better opportunities for Chinese language learning in remote areas. In this article, we have concisely compiled the data of major Confucius institutes, and their potential to provide Chinese learning opportunities with statistical analyses of Chinese learners for HSK, HSKK, and YCT programs with critical trend discussion. Results elucidated that the trend of Chinese learning was continuously increasing till 2018 then declined. The reasons for this decline, their possible solutions, and the future of teaching Chinese in Pakistan has been discussed which will help with scenario analyses and perspectives.